Population-Based Evaluation of Indirect Signs of Increased Intracranial Pressure. Issue 1 (March 2022) - Witsberger, Emily M.; Huston, John; Cutsforth-Gregory, Jeremy K.; Johnson, Patrick W.; Bhatti, M. Tariq; Chen, John J.
Abstract : Background: The Mayo Clinic Study of Aging (MCSA) is a unique prospective study that systematically evaluates the normal aging population and includes many participants undergoing both MRI and lumbar puncture (LP). Using MCSA date, we aimed to determine the prevalence of indirect signs of raised intracranial pressure (ICP) on MRI and whether these correlate with LP opening pressure (OP). This is a large-scale study that evaluates how often indirect signs of increased ICP occur in a normal population. Methods: MCSA participants who had an MRI within 3 months of an LP with recorded OP were included in the study. MRIs were reviewed for indirect signs of raised ICP, including pituitary to sella (P/S) ratio, cerebellar tonsillar ectopia, and optic nerve sheath diameter (ONSD). These signs were evaluated for correlations with OP and influences from body mass index (BMI) and obstructive sleep apnea (OSA). Results: Five hundred ninety-seven MCSA patients were identified who underwent both LP and MRI. Two hundred sixty (43.6%) were women. The median age was 70.7 years (range 32.6–92.7). Median OP was 152 mm H2 O (range 60–314 mm H2 O), with 91 (15.2%) participants having an OP ≥ 200 mm H2 O. Empty or partially empty sella was seen in 81 (12.8%) of the cohort. The P/S ratio decreased with increasing OP (r = −0.3, P < 0.001). There was a weak correlation between OP and average ONSD (r = 0.184, P = 0.01), which was no longer significant when accounting for age, gender, and BMI (partial r 2 = 0.014, P = 0.097). There was no correlation between OP and cerebellar tonsillar ectopia. OSA was associated with increased ONSD ( P = 0.004), but this did not remain statistically significant after accounting for age, gender, and BMI ( P = 0.085). Conclusion: Smaller pituitary gland size correlated with increasing OP. This suggests that ICP is a continuum with some normal individuals demonstrating asymptomatic radiologic signs of raised ICP.